KERJASAMA INDONESIA DAN RUSIA DALAM PENGEMBANGAN SEKTOR PARIWISATA PERIODE 2012-2016 - Bella Fauzia Feriksca, - (2018)
This research deals with "Cooperation between Indonesia and Russia in tourism sector Period 2012-2016". To answer the research authors use qualitative method where the author seeks to provide an explanation regarding the Memorandum of Understanding and the implementation of the government's tourism marketing development Indonesia Russia tourist 2012-2016, as well as primary and secondary document gathering through interviews and analysis document. The author uses the framework of thought the National Interest, International Cooperation, Bilateral Relations, Tourism Concept, Strategic Plan and Tourist. The result of this research show that the implementation development the government does give a pretty good impact, where each year 2012-2016 an increase in tourist visits Russia to Indonesia